Can labor market imperfections explain changes in the inverse farm size-productivity relationship? Longitudinal evidence from rural India - Deininger, Klaus; Jin, Songqing; Liu, Yanyan; Singh, Sudhir K. (International Food Policy Research Institute, 2016)
To understand whether and how inverse relationship between farm size and productivity changes when labor market performance improves, we use large national farm panel from India covering a quarter-century (1982, 1999, 2008) to show that the inverserelationship weakened significantly over time, despite an increase in the dispersion of farm sizes. A key reason was the substitution of capital for labor in response to nonagricultural labor demand. In addition, family labor wasmore efficient than hired labor in the 1982–1999 period, but not during the 1999–2008period.In line with labor market imperfections as a key factor, separability of labor supply and demand decisions cannot be rejected in the second period,except in villages with very low nonagricultural labor demand.